Chemical self-assembly strategies for designing molecular electronic circuits. Issue 92 (1st November 2019) - Olson, Dustin; Boscoboinik, Alejandro; Tysoe, Wilfred T.
Abstract : Design principles are demonstrated for fabricating molecular electronic circuits using the inherently self-limiting growth of molecular wires between gold nanoparticles from the oligomerization of 1, 4-phenylene diisocyanide. Abstract : Design principles are demonstrated for fabricating molecular electronic circuits using the inherently self-limiting growth of molecular wires between gold nanoparticles from the oligomerization of 1, 4-phenylene diisocyanide.